2005
DOI: 10.1080/10810730590950057
|View full text |Cite
|
Sign up to set email alerts
|

Messages from Teens on the Big Screen: Smoking, Drinking, and Drug Use in Teen-Centered Films

Abstract: Smoking, drinking, and drug use endure as popular yet dangerous behaviors among American teenagers. Films have been cited as potential influences on teens' attitudes toward and initiation of substance use. Social cognitive theory suggests that teen viewers may be especially likely to learn from teen models who they perceive as similar, desirable, and attractive. Yet, to date, no studies systematically have analyzed teen characters in films to assess the frequency, nature, and experienced consequences of substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 36 publications
4
60
0
Order By: Relevance
“…Few differences were found between drinkers and non-drinkers in terms of physical attractiveness, socio-economic status, gender or virtuousness, and drinkers were rarely shown refusing offers to drink, regretting drinking, or indeed suffering any consequences -negative or otherwise -from alcohol consumption. Stern (2005) concludes that the overall message conveyed in films targeted towards a predominantly teen audience is that alcohol consumption in this age group is common, mostly risk-free, and appropriate for anyone.…”
Section: Filmmentioning
confidence: 99%
See 2 more Smart Citations
“…Few differences were found between drinkers and non-drinkers in terms of physical attractiveness, socio-economic status, gender or virtuousness, and drinkers were rarely shown refusing offers to drink, regretting drinking, or indeed suffering any consequences -negative or otherwise -from alcohol consumption. Stern (2005) concludes that the overall message conveyed in films targeted towards a predominantly teen audience is that alcohol consumption in this age group is common, mostly risk-free, and appropriate for anyone.…”
Section: Filmmentioning
confidence: 99%
“…Since the late 1970s much research has thus focused on studying the portrayal of alcohol in popular television entertainment programming, notably television drama serials (soaps) and series, while a significant but less prolific body of research has also emerged into the portrayal of alcohol and drinking in other genres and media, such as film (Cook & Lewington, 1979;Denzin, 1991;Roberts, Henriksen, & Christenson, 1999;Stern, 2005), radio (Pitt, Forrest, Hughes, & Bellis, 2003;Daykin, Irwin, Kimberlee, Orme, Plant, McCarron, et al, 2009), popular music lyrics (Cruz, 1988;Herd, 2005), popular fiction (Cellucci & Larsen, 1995;Greenman, 2000) and music videos (DuRant, Rome, Rich, Allred, Emans, & Woods, 1997;Robinson, Chen, & Killen, 1998;Van den Bulck & Beullens, 2005;Beullens & Van den Bulck, 2008). Given the rapid growth and popularity of the internet, mobile phones and related new media technologies in the last 10-15 years, it is perhaps surprising that only a small number of studies (e.g.…”
Section: Alcohol In Entertainmentmentioning
confidence: 99%
See 1 more Smart Citation
“…But not only respondent's perceptions and intended actions are studied. There are studies look closer at drug abuse and other related substance abuse like alcohol in movies and films from a health perceptive (Stern, 2005) and what primary care practitioners need to know about the influence of the media on adolescents Strasburger (2006). Risky content as tobacco is primarily studied in relation to anti-smoking messages.…”
Section: General Support Of Occurrence Of Tpe Among Children Is Not Tmentioning
confidence: 99%
“…Indeed, in their analysis of the most popular movie rentals from 1996 to 1997, Roberts et al (1999) found that 22% of characters who appeared to be under the age of 18 were shown drinking alcohol. More recently, Stern (2005) found that two-fifths of the teenage characters in the most successful teen-centred films from 1999-2001 were shown drinking. Moreover, of all characters shown drinking alcohol, more than half were depicted as drunk, and almost a tenth were shown driving while drunk.…”
mentioning
confidence: 99%